Stocks and oxidizable fractions of soil organic matter under organic coffee agroforestry systems - Guimarães, Gabriel Pinto; Mendonça, Eduardo de Sá; Passos, Renato Ribeiro; Andrade, Felipe Vaz (Coffee Science - ISSN 1984-3909, 2014)
Research evaluating the impact of different management systems coffee are essential for determining soil quality. The objective of this study was to evaluate the impact of production systems for organic coffee and agroforestry on stocks of carbon, nitrogen and organic matter quality in two farms in the region Caparaó- Espírito Santo- Brazil. In farm 1 systems were evaluated primary forest, organic coffee and conventional coffee. In farm 2 systems were evaluated secondary forest, organic coffee intercropped with inga, organic coffee intercropped with leucaena and inga, organic coffee intercropped cedar and conventional coffee full sun. Soil samples were collected in canopy projection coffee in the depths 0-10, 10-20, 20-40, 40-60 and 60-100 cm. The C and N stock reflected the management history in relation to forest areas, with the greatest impact in the 0-10 cm. This depth, to the farm 1, the conventional coffee obtained reductions of 27.3 % and 14.9 % respectively in C and N stocks in relation to organic coffee. For farm 2, reductions in C and N stocks the coffee conventional full sun in relation to agroforestry coffee were 22.1 % and 31.4 %, respectively. The C stocks accumulated were reduced in coffee systems in 28.6 % and 17.4 % respectively in relation to primary and secondary forests. The mineralizable C content was higher in the soil surface layers and in the organic coffee systems compared to conventional coffee, in the farm 2. The coffee agroforestry system provided higher carbon management index in relation to organic coffee without consortium and conventional coffee, providing better soil quality.